1997
DOI: 10.1023/a:1025731529006
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Research has demonstrated a high prevalence of language impairments (LI) and reading disabilities (RD) in children with attention deficit hyperactivity disorder (ADHD). Since RD is also associated with LI, it is unclear whether the language impairments are specific to ADHD or associated with comorbid RD. The language abilities of ADHD children with and without RD were investigated in a task requiring recall of a lengthy narrative, and in tests assessing knowledge of the semantic aspects of language. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(58 citation statements)
references
References 31 publications
5
51
0
2
Order By: Relevance
“…Kim & Kaiser, 2000;Purvis & Tannock, 1997). However, this study confirmed earlier findings (e.g., Barini & Hage, 2015;Purvis & Tannock, 1997) that children with ADHD have verbal comprehension difficulties.…”
Section: Language Domainsupporting
confidence: 91%
See 1 more Smart Citation
“…Kim & Kaiser, 2000;Purvis & Tannock, 1997). However, this study confirmed earlier findings (e.g., Barini & Hage, 2015;Purvis & Tannock, 1997) that children with ADHD have verbal comprehension difficulties.…”
Section: Language Domainsupporting
confidence: 91%
“…Kim & Kaiser, 2000;Purvis & Tannock, 1997). However, this study confirmed earlier findings (e.g., Barini & Hage, 2015;Purvis & Tannock, 1997) that children with ADHD have verbal comprehension difficulties. It is of note that we used Comprehension of Instructions subtest, which demands the ability to receive, process, and execute instructions of increasing syntactic complexity, which may have further increased the working memory load.…”
Section: Language Domainsupporting
confidence: 91%
“…The small sample size, use of participants from one geographic area, and particular demographics of the population should be taken into account when attempting to generalize the results. It can be noted also that previous studies have been published on the subject matter with fewer study participants (Purvis & Tannock, 1997). In addition, students in the study were all a part of a larger research study and the sample was not randomly chosen.…”
Section: Limitationsmentioning
confidence: 99%
“…A longitudinal study which assessed 200 children at age ten, thirteen, seventeen, and twenty seven found that during middle childhood the children rated as having high levels of inattentiveness and hyperactivity were also rated as poor readers with more behavior problems (Willcutt & Pennington, 2000). Other studies have found a link between students who fit the criteria for ADHD and reading disabilities (Ghelani et al, 2004;Purvis & Tannock, 1997) and or behavior problems (Maughan et al, 1996). Maughan et al (1996) focused on reading problems and antisocial behavior in twins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation